2020
DOI: 10.1126/science.abb7699
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale RNAi screening uncovers therapeutic targets in the parasite Schistosoma mansoni

Abstract: Schistosome parasites kill 250,000 people every year. Treatment of schistosomiasis relies on the drug praziquantel. Unfortunately, a scarcity of molecular tools has hindered the discovery of new drug targets. Here, we describe a large-scale RNA interference (RNAi) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
74
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(76 citation statements)
references
References 61 publications
(31 reference statements)
2
74
0
Order By: Relevance
“…Consequently, there is a drive to develop a new generation of therapeutics based on schistosome genomes and their function (e.g. Berriman et al, 2009;Crosnier et al, 2020;Wang et al, 2020). Understanding the rhythms of target genes and their products will determine how an organ, or organism, will respond to a drug at a specific time of the day, and the timing of drug delivery could have a large impact on the effectiveness of target activation or inhibition (Cederroth et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Consequently, there is a drive to develop a new generation of therapeutics based on schistosome genomes and their function (e.g. Berriman et al, 2009;Crosnier et al, 2020;Wang et al, 2020). Understanding the rhythms of target genes and their products will determine how an organ, or organism, will respond to a drug at a specific time of the day, and the timing of drug delivery could have a large impact on the effectiveness of target activation or inhibition (Cederroth et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Understanding the rhythms of target genes and their products will determine how an organ, or organism, will respond to a drug at a specific time of the day, and the timing of drug delivery could have a large impact on the effectiveness of target activation or inhibition (Cederroth et al, 2019). An RNAi screen to uncover new therapeutic targets in S. mansoni identified 195 genes that caused parasite detachment and affected survival (Wang et al, 2020), eight of which we have identified as diel genes (Additional file 1: Table S4), including Hsp90 (Smp_072330) that demonstrated very high amplitudes in both sexes. By searching the ChEMBL database (Mendez et al, 2019), we identified existing drugs that are predicted to target the encoded protein of 26 diel genes, 12 of which are phase IV approved drugs (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, this pathway has been exploited as a reverse genetic tool to silence specific genes (Han, 2018). Currently, more than two decades after it was first applied to a flatworm species (Sańchez Alvarado and Newmark, 1999), it is still the main tool to study gene function in worms (Mourão et al, 2012;Wang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…These parasitic organisms are well suited for genetic studies because (i) the complete lifecycle can be maintained in the laboratory using rodent definitive hosts and freshwater snail intermediate hosts, (ii) parasites have separate sexes which simplifies staging of efficient genetic crosses in the laboratory, (iii) thousands of progeny are produced which provides good statistical power, and (iv) experimental work over the last 75 years has revealed heritable genetic variation in multiple biomedically important traits (Anderson et al, 2018) such as drug resistance (Cioli et al, 1992;Greenberg, 2013;Melman et al, 2009;Mwangi et al, 2014;Valentim et al, 2013), chronobiology (Théron, 2015;Théron andCombes, 1983, 1988), host specificity (Files and Cram, 1949;Kalbe et al, 2004;Mitta et al, 2017;Rollinson et al, 2001;Theron et al, 2014), and virulence (Davies et al, 2001;Gower and Webster, 2004;Webster et al, 2004). Furthermore, the Schistosoma mansoni genome is fully sequenced and assembled (Berriman et al, 2009;Protasio et al, 2012), and a growing molecular toolkit including molecular sexing tools (Chevalier et al, 2016;Gasser et al, 1991), RNAi (Krautz-Peterson et al, 2010), transfection (Mann et al, 2014;Rinaldi et al, 2012), CRISPR (Ittiprasert et al, 2019;Sankaranarayanan et al, 2020;You et al, 2021) and a suite of cell biology tools (Collins and Collins, 2017;Wang et al, 2020;Wendt et al, 2020;Wendt and Collins, 2016) improves our ability to link phenotype with genotype. Furthermore, we can also control the genetics of the snail host by generating inbred snail lines.…”
Section: Introductionmentioning
confidence: 99%